Comportamento e correção da radiação solar difusa obtida com o anel de sombreamento - Drechmer, Patricia Aparecida de Oliveira (2005)
This paper shows the comportment of solar radiation global, direct and diffuse radiation at Cascavel, classifies the sky s cover in function of the cloudiness index and studies the applicability of the numeric correction of RICIERI (1998) on diffuse radiation measured with a shadow ring. The research was done at meteorological experimental station of UNIOESTE, Cascavel. The solar radiation components were monitored from January 03, 2001 to February 14, 2003. The global radiation was monitored by a pyranometer KIPP & ZONEN-CM3 and the direct radiation were monitored by a pyrheliometer EPPLEY-NIP coupled to a solar tracer. The diffuse radiation was monitored by the difference between global radiation and direct radiation projected over the horizontal surface and by a pyranometer covered by a shadow ring. The monthly average levels of the global, direct and diffuse irradiations were 51,8%, 31,7% and 20,17% of the irradiation over the atmosphere s top. The diffuse irradiation measured by the difference method and by the shadow ring method corrected by DRUMMOND s factor and compared through the relative daily deviation. It was observed that, in 94% of the days, the diffuse radiation by DRUMMOND s factor was lower than the difference method. The deviations were higher for cloudless days (19,82%), than for partially cloudy days (9,55%) and cloudy days (2,68%). The RICIERI s correction (1998), that proposes the correlation of diffuse irradiation without correction with the diffuse irradiation by the difference method, was used and the linear function Rd=0,16545+1,21715R d was found to correct the diffuse by the shadow ring method. This correction increases the precision of the diffuse fraction obtained by shadow ring, decreasing the average relative deviation from 11,79%, when the DRUMMOND s correlation was applied, to 7,37%. In order to increase the model s precision, it was proposed the partial numeric equation fitted in function of the sky s cover. It was verified decrease mean values of relative deviation, when compared with the DRUMMOND s correction: 4,8% in cloudless sky, 4,66% in partially cloudy sky and, 4,6% in cloudy sky. The average relative deviation was 4,68%. The diffuse solar radiation measured on Cascavel-PR and corrected by RICIERI s numeric function, determined to region of Botucatu - SP, shows relative deviation to cloudy sky, partially cloudy sky and cloudless sky, respectively, 4,6%, 4,8% and 5,29%, suggesting that the functions developed to Botucatu - SP tend to be independent from the locality.